Teaching Indonesian as a foreign language through Small Private Online Course (SPOC): investigating learners' multidimensional anxiety in online learning - Darmawansah, Darmawansah (Universitas Negeri Yogyakarta, 2020)
One of the foreign language learners challenges is the anxious level they mostly face while learning a new language. Even though Foreign Language Anxiety (FLA) has been analyzed for decades to foresee language learners' challenges in the learning process, the previous results only focus on single language skills and the offline learning environment. In consideration, learning a foreign language is supposed to be a multidimensional analysis and forced to be online due to the current pandemic. Thus, this study investigates how Taiwanese learners face FLA when learning Indonesian as A Foreign Language (IFL) through Small Private Online Course (SPOC). Participants were assessed by Multimedimensional Language Anxiety Scale (MLAS) at the end of their six-months course. The results showed that writing was the highest anxiety while reading was the lowest anxiety. The psychology domain that showed the learners tension during learning IFL through SPOC revealed the most highly anxious. Surprisingly, nearly two-thirds of learners were considered overall moderate-level anxiety by using SPOC as a learning platform. In further investigation, male learners dominated each foreign language skills and domains' anxiety level compared to female learners. The correlations among language skills and domains are presented and critically discussed. Finally, it opens more opportunities to explore SPOC and another online learning platform to reduce learners' FLAs